F2 tornado velocity profiles critical for transmission line structures. (1st January 2016) - El Damatty, A.A.; Hamada, A.
Abstract: In several locations around the globe, many failures of transmission line structures have been observed during high intensity wind events in the form of tornadoes and downbursts. There is a lack of procedures in the design codes and manuals of practice related to the estimation of tornado forces on transmission line systems. As such, the purpose of this paper is to present load cases that simulate the critical effect of F2 tornadoes on tangent lattice transmission line structures. The current study builds on extensive research previously conducted at the University of Western Ontario, Canada on this subject. A main challenge in this application of localized wind events is that the forces acting on the structure vary significantly based on the location of the tornado and a large parametric study involving varying the tornado location has to be conducted for each system to determine critical cases. Critical load cases are determined in this study based on parametric studies carried out in previous investigations as well as others conducted in the current study. The vertical profile of three velocity components associated with each critical load case as well as the horizontal profile of the associated transverse velocity along the lines are provided in this paper. A procedure that will allow practicing engineers to use those profiles for analyzing lattice transmission lines under F2 tornadoes is described. Validation of the developed procedure is conducted by considering two independent transmission line systems. The results indicate that the developed load cases estimates peak internal forces that are either slightly higher or 5% less than the values predicted by the detailed parametric studies.